On the Absorption and Photoluminescence Properties of Pure ZnSe and Co-Doped ZnSe:Eu3+/Yb3+ Crystals - Behnaz Abbasgholi-NA; Osamah A. Aldaghri; Khalid Hassan Ibnouf; Nawal Madkhali; Humberto Cabrera (Applied Sciences, 2022)
Co-doped Zinc selenide (ZnSe) is a promising material because of a high photoluminescence efficiency and wide spectral range emission in the visible region. In this work, ZnSe and Eu3+/Yb3+ co-doped ZnSe crystals were grown by the chemical vapour transport method. Photoluminescence and optical measurements revealed the effect of trivalent rare earth Eu3+/Yb3+ ions on the emission of new lines with enhancement intensity. In the photoluminescence spectrum, some sharp and intense lines were observed that allow for the possibility of covering a broad emission range. Moreover, the optical measurement showed a lower bandgap compared to that of pure ZnSe bulk crystal. This material is suitable for developing optoelectronic devices, which can emit light in the visible and near infrared range with an improved emission efficiency and wide tunability.